Monoaminergic System Modulation in Depression and Alzheimer’s Disease: A New Standpoint? - Morgese, Maria Grazia; Trabace, Luigia (Frontiers in Pharmacology, 2019)
The prevalence of depression is dramatically increased and it has been esteemed that over 300 million people suffer from depression all over the world. Depression is highly comorbid with many central and peripheral disorders. In this regard, depressive states have been associated with the development of neurological disorders such as Alzheimer’s disease (AD). Accordingly, depression is a risk factor for AD and depressive symptomatology is common in pre-clinical AD representing an early manifestation of this disease. Neuropsychiatric symptoms may represent prodromal symptoms of dementia deriving from neurobiological changes in specific cerebral regions, thus the search for common biological substrates is becoming imperative and intriguing field of research. Soluble forms of beta amyloid peptide (Aβ) have been implicated both in the development of early memory deficits or neuropsychiatric symptoms. Indeed, soluble Aβ species have been shown to induce depressive-like phenotype in AD animal models. Alterations in monoamine content is a common feature of these neuropathologies. Interestingly, serotonergic system modulation has been implicated in alteration in Aβ production. In addition, noradrenaline is considered crucially involved in compensatory mechanisms leading to increased Aβ degradation via several mechanisms, included microglia modulation. In further agreement, antidepressant drugs have been shown to potentially modulate also cognitive symptoms in AD and depression. Thus, the present review summarizes the main knowledge about biological and pathological substrates, such as monoamine and related molecules, commonly involved in AD and depression pathology thus shading light on new therapeutic approaches.